Phase behavior of polymer blends - Freed, Karl F. (Advances in polymer science, 2005)
D. Schwahn: Critical to mean field crossover in polymer blends - K.F. Freed, J. Dudowicz: Influence of monomer molecular structure on the miscibility of polymer blends - N. Clarke: Effect of shear flow on polymer blends.